The Influence of Principal Leadership and Teacher Dicipline on Teacher Performance - Intan Rahmayuni Syafitri; Taufik Hendra; Nurhizrah Gistituati (IAIN Batusangkar, 2022)
The purpose of this study is to determine whether or not there is an influence of a principal's leadership and work discipline on the performance of a teacher at SMP Negeri 8 Padang. This research includes qualitative research in the form of case studies. Those appointed as resource persons are teachers and school principals, whose data is taken by conducting observations, interviews, and documentation. The results obtained from this study are 1) The principal's leadership style acts in teacher performance. The effectiveness of a principal's leadership style can motivate teacher performance in schools, 2) Work discipline plays an important role for teacher performance, because whether or not the teacher's discipline attitude will make teachers have the will to comply with the rules that have been made by the school, and 3 ) Teacher performance and work discipline can increase if the leadership style of a school principal is effective. So the interaction between the principal's leadership style and work discipline affects the performance of teachers in schools.